New Zealand : 2021 Article IV Consultation-Press Release; Staff Report; Staff Statement; and Statement by the Executive Director for New Zealand. (IMF Staff Country Reports; Country Report ;, 2021)
New Zealand's sound management of the COVID-19 crisis has been effective in bringing infection rates quickly under control. Decisive fiscal and monetary policy responses have been instrumental in cushioning the economic impact. Although economic activity was hit hard initially, it has recovered faster than expected. That said, the recovery has been uneven, with some sectors and workers disproportionately affected.